Effect of Backing Plate Materials in Micro-Friction Stir Butt Welding of Dissimilar AA6061-T6 and AA5052-H32 Aluminum Alloys - SeongHwan Park; YoungHwan Joo; Myungchang Kang (Metals, 2020)
Thin sheets of lightweight aluminum alloys, which are increasingly used in automotive, aerospace, and electronics industries to reduce the weight of parts, are difficult to weld. When applying micro-friction stir welding (μ-FSW) to thin plates, the heat input to the base materials is considerably important to counter the heat loss to the jig and/or backing plate. In this study, three different backing-plate materials—cordierite ceramic, titanium alloy, and copper alloy—were used to evaluate the effect of heat loss on weldability in the μ-FSW process. One millimeter thick AA6061-T6 and AA5052-H32 dissimilar aluminum alloy plates were micro-friction stir welded by a butt joint. The tensile test, hardness, and microstructure of the welded joints using a tool rotational speed of 9000 rpm, a welding speed of 300 mm/min, and a tool tilting angle of 0° were evaluated. The heat loss was highly dependent on the thermal conductivity of the backing plate material, resulting in variations in the tensile strength and hardness distribution of the joints prepared using different backing plates. Consequently, the cordierite backing plate exhibited the highest tensile strength of 222.63 MPa and an elongation of 10.37%, corresponding to 86.7% and 58.4%, respectively, of those of the AA5052-H32 base metal.